PENGARUH POLA GERAK BINATANG TERHADAP KEPERCAYAAN DIRI ANAK USIA 5-6 TAHUN DI TK AN-NISA KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Sari, Bulan Purnama; ', Zulkifli N; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrac: Based on the observation at school there were founded some problems as bellows: 1) There is some child who are afraid to show up/ perform in of the class, 2) some of them don’t want to share their ideas, 3) there are the ignorance of child to do the activities, 4) the child are also afraid to answer the question, 5) there is also child who doesn’t want to join with other child. The population and the sample that used in this research are 15 children. The data collection technique is observation sheet. The data technique is T-Test by using SPSS windows ver. 22. Hopefully this research’s result is useful as broad insight to increase child’s self confidence in TK An – Nisa in Marpoyan Damai District Pekanbaru. Based on the first description of the analysis in TK An – Nisa in Marpoyan Damai District Pekanbaru is the low level, it shown based on the Pretest is 179 by the average 13, 33. After gave the animals’ movement treatment, so to the next is to determine Post test that found 301 by the average 20,067, the child before the animal’s movement treatment is “Good” level by 0% and “Enough” level by 33,33% meanwhile in “Low” level is 66,67%.Keywords: Movement feature, self confident